SP0196 Obesity and Diet in Experimental Models of OA. (15th July 2016) - Griffin, T.
Abstract : Obesity is a significant modifiable risk factor for osteoarthritis in both weight bearing and non-weight bearing joints. Pre-clinical animal models of diet-induced obesity and genetic models of obesity provide new insight into the pathogenesis of obesity-induced osteoarthritis and the underlying cellular and molecular mechanisms involved in this process. Multiple mechanisms appear to be responsible for this increased risk, including biomechanical, inflammatory, post-traumatic, genetic, and metabolic factors. A central finding of many of these studies is that increased dietary lipids and adiposity promote osteoarthritis pathology, even independent of weight gain. Adipose tissue inflammation is considered a central mechanism by which obesity increases osteoarthritis risk, and I will present evidence from the literature and our recent findings that explore this link in obese animal models, focusing on systemic versus local sources (e.g., abdominal versus infra-patellar fat pad). These findings indicate that the infra-patellar fat pad is a source of inflammatory mediators but does not recapitulate the pathogenesis of inflammation that occurs with abdominal adiposity. Additional evidence suggests that obesity alters pathways regulating chondrocyte metabolism. I will discuss these findings and present a working model for how obesity-associated increases in chondrocyte lipid metabolism may impair the homeostatic response of chondrocytes to biomechanical and inflammatory stresses. Disclosure of Interest: None declared